2017
DOI: 10.1021/acs.molpharmaceut.7b00569
|View full text |Cite
|
Sign up to set email alerts
|

Large Amino Acid Transporter 1 Selective Liposomes of l-DOPA Functionalized Amphiphile for Combating Glioblastoma

Abstract: Despite significant progress in neurosurgery and radiation therapy during the past decade, overall survivability (OS) of glioblastoma patients continues to be less than 2 years. The scope of systemic chemotherapy is greatly limited by poor drug transport across the blood brain barrier (BBB) and, thereby, suboptimal drug accumulation in glioma tissue. To this end, use of large amino acid transporter-1 (LAT1) overexpressed both on brain capillary endothelial cells (BCECs) and glioma cells has begun. Prior report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…All cells were maintained at 37°C in a humidified incubator containing 5% CO 2 and were washed with phosphate-buffered saline (PBS) and harvested with trypsin as necessary. LAT1 expression of these cells were confirmed in previous studies [16,23].…”
Section: In Vitro Cellular Uptake and Inhibition Assaysupporting
confidence: 85%
See 1 more Smart Citation
“…All cells were maintained at 37°C in a humidified incubator containing 5% CO 2 and were washed with phosphate-buffered saline (PBS) and harvested with trypsin as necessary. LAT1 expression of these cells were confirmed in previous studies [16,23].…”
Section: In Vitro Cellular Uptake and Inhibition Assaysupporting
confidence: 85%
“…Moreover, we demonstrated the functional expression of LAT1 in these tumors using histology and western blot analyses [5,15]. A western blot analysis of GL261 cells also revealed strong expression of LAT1 [16]. In our current in vitro cellular uptake analysis, we demonstrated the transport of 211 At-PA via system L amino acid transporters.…”
Section: Discussionmentioning
confidence: 57%
“…In vivo studies showed that glutamate-conjugated liposomes could effectively cross the BBB and selectively distribute into the brain. Similar results were obtained with L-DOPA-conjugated liposomes, again targeting LAT1 in BBB and glioma [ 85 ].…”
Section: Transporter-targeted Ndds For Enhancing Bbb Permeationsupporting
confidence: 83%
“…In the biodistribution study, the NIR-dye labelled liposomes of Amphi-Dopa were detected in the brain, liver and spleen at 4 h after i.v. administration but predominantly in the brain at 24 h in glioblastoma-bearing mice (94). The i.v.…”
Section: Delivery Of Anticancer (Pro)drugsmentioning
confidence: 96%
“…injection of fluorescent-labelled nanoparticles in glioma model nude mice without any signs of systemic toxicity (93). In another study, Bhunia et al (2017) developed LAT1 a selective liposomal drug carrier prepared from a novel L-Dopa functionalized amphiphile (Amphi-Dopa) (94). In the biodistribution study, the NIR-dye labelled liposomes of Amphi-Dopa were detected in the brain, liver and spleen at 4 h after i.v.…”
Section: Delivery Of Anticancer (Pro)drugsmentioning
confidence: 99%